Saxifrago ferdinandi-coburgi-Seslerietum actarovii – a new association from the subalpine belt of the Slavianka (Orvilos) Mts. (Bulgaria ) - Karakiev, Todor; Tzonev, Rossen (Hacquetia, 2015)
The paper discusses the phytosociological and syntaxonomical position of the dry subalpine grasslands in the Slavianka (Alibutoush, Orvilos) Mts. (South-Western Bulgaria, Northern Greece). A new association Saxifrago ferdinandi-coburgi-Seslerietum actarovii ass. nova has been established as a result of the phytosociological study. It is considered as an endemic vegetation unit from the calcareous subalpine terrains in the Central Balkan Peninsula high mountains (SouthWestern Bulgaria, Former Yugoslav Republic of Macedonia, Northern Greece). The new syntaxon belongs to the alliance Edrajantho-Seslerion Horvat 1949. A comparison with related syntaxa from other calcareous mountains from Northern Greece and the Former Yugoslav Republic of Macedonia is discussed.